Creating Old World Wisconsin : The Struggle to Build an Outdoor History Museum of Ethnic Architecture - Krugler, John D., 1940- (Book collections on Project MUSE., 2013)
With its charming heirloom gardens, historic livestock breeds, and faithfully recreated farmsteads and villages that span nearly 600 acres, Old World Wisconsin is the largest outdoor museum of rural life in the United States. The site, created and maintained by the Wisconsin Historical Society, offers visitors a unique opportunity to learn about the state's rich and ethnically diverse past through depictions of the everyday lives of its Norwegian, Danish, Finnish, German, Polish, African American, and Yankee inhabitants. This book chronicles the fascinating and complex origins of this outdoor museum, highlighting the struggles that faced its creators as they worked to achieve their vision.